2021
DOI: 10.1126/sciadv.abh4048
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of strigolactone-producing bacterium-yeast consortium

Abstract: Strigolactones (SLs) are a class of phytohormones playing diverse roles in plant growth and development, yet the limited access to SLs is largely impeding SL-based foundational investigations and applications. Here, we developed Escherichia coli-Saccharomyces cerevisiae consortia to establish a microbial biosynthetic platform for the synthesis of various SLs, including carlactone, carlactonoic acid, 5-deoxystrigol (5DS; 6.65 ± 1.71 g/liter), 4-deoxyorobanchol (3.46 ± 0.28 g/liter), and orobanchol (OB; 19.36 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 85 publications
0
33
0
Order By: Relevance
“…Recently, it was reported that in a co-culture system of Escherichia coli and Saccharomyces cerevisiae co-expressing SL biosynthesis genes, orobanchol is generated by the co-expression of VuCYP722C with the upstream SL biosynthesis genes. However, the production of its diastereomer has not been described ( Wu et al, 2021 ). Therefore, a more detailed functional analysis of the CYP722C subfamily is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that in a co-culture system of Escherichia coli and Saccharomyces cerevisiae co-expressing SL biosynthesis genes, orobanchol is generated by the co-expression of VuCYP722C with the upstream SL biosynthesis genes. However, the production of its diastereomer has not been described ( Wu et al, 2021 ). Therefore, a more detailed functional analysis of the CYP722C subfamily is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…For CL production, XY medium [13.3 g/l monopotassium phosphate (KH 2 PO 4 ), 4 g/l diammonium phosphate [(NH 4 ) 2 HPO 4 ], 1.7 g/l citric acid, 0.0025 g/l cobalt(II) chloride (CoCl 2 ), 0.015 g/l manganese(II) chloride (MnCl 2 ), 0.0015 g/l copper(II) chloride (CuCl 2 ), 0.003 g/l boric acid (H 3 BO 3 ), 0.0025 g/l sodium molybdate (Na 2 MoO 4 ), 0.008 g/l zinc acetate [Zn(CH 3 COO) 2 ], 0.06 g/l iron(III) citrate, 0.0045 g/l thiamine, 1.3 g/l magnesium sulfate (MgSO 4 ), 5 g/l yeast extract, and 40 g/l xylose, pH 7.0] was prepped and used as previously described ( Wu et al, 2021 ). For yeast ectopic expression, synthetic dropout (SD) medium (SDM) was used [0.425 g yeast nitrogen base (YNB) (BD Biosciences, San Jose, CA, United States), 1.25 g ammonium sulfate [(NH 4 ) 2 SO 4 ] dissolved in 200 ml distilled water (dH 2 O), autoclave at 121°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The E. coli strain ECL for CL production ( Supplementary Table 3 ) was prepared as described previously ( Wu et al, 2021 ). Single colony was grown overnight at 37°C in 1 ml Luria-Bertani (LB) containing 25 μg/ml chloramphenicol, 50 μg/ml spectinomycin, and 100 μg/ml ampicillin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations